Topical co-delivery of indomethacin and nigella sativa L. essential oil in poly-cappa-caprolactone nanoparticles: in vitro study of anti-inflammatory activity - Badri, Waisudin; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi; El Asbahani, A.; Miladi, Karim; Nazari, Qand Agha; Viennet, Celine; Robin, Sophie; Fessi, Hatem; Elaissari, Abdelhamid (International Journal of Advanced Research (IJAR), 2018)
Indomethacin is a potent, nonselective Non-steroidal Antiinflammatory Drug (NSAID) but its low water-solubility precludes its use as topical dosage form. As with other NSAIDs, the systemic delivery is associated with high risk of serious gastrointestinal adverse events including bleeding, ulceration and perforation of stomach and intestines. Here we demonstrate a safer way of administration i.e via topical demonstrating synergistic effects when co-delivered with Nigella sativa L. seeds essential oil (NSSEO) in the form of coencapsulated particles (~200 nm) of poly--caprolactone. The particles showed penetrability across stratum corneum to dermis layer in ex-vivo human skin. Further study in the xyline-induced ear edema in mice was performed, and co-encapsulated particles demonstrated highest antiinflammatory effect compared to indomethacin particles and indomethacin gels. Despite slower onset compared to indomethacin gels, the inflamed ear continued to show reduction in thickness over 8 hours of observation demonstrating synergistic and pro-longed effect contributed by NSSEO. In immunohistochemistry study of CD45+, the mice ears treated with co-encapsulated particles showed considerable reduction in lesions, epidermal-dermal separation and inflammatory cells (lymphocytes and neutrophils) infiltration as compared to other formulation. Based on microscopic evaluation, the anti-inflammatory inhibition effect of co-encapsulated particles is the highest (90%) followed by indomethacin particles (79%) and indomethacin gel (49%). The findings suggest not only skin permeability of indomethacin significantly improved but also the therapeutic effects, all provided by the presence of NSSEO in the particles. This study paves the way to more co-encapsulation of any other contemporary medicines in combination with this wholesome natural oil, NSSEO.